Kontribusi BAZNAS dalam Meningkatkan Kesejahteraan Masyarakat Melalui Penanganan Kemiskinan Di Kabupaten Enrekang - Kamariah, Kamariah (ITB AAS INDONESIA Surakarta, 2024)
Abstract This research was conducted to determine the level of Baznas' role or contribution to improving community welfare in order to assist sustainable development goals in Enrekang Regency in terms of the programs and policies that Baznas Enrekang has implemented so far in managing zakat funds. The method used in this research is a qualitative method and a descriptive analysis approach model with the acquisition of managed data, namely secondary data or in the form of program reports in institutions or the National Amil Zakat Agency in Enrekang Regency and other policies as well as data sourced from the Enrekang Regency Baznas website owned or the website of the central Baznas or the website of the SDGs program itself, apart from that secondary data was also used which was obtained through direct or indirect interview techniques with respondents, observations and literature reviews were also carried out from other sources. The results of this research show that the contribution of Baznas Enrekang Regency in realizing sustainable development programs (SDGs) in terms of community welfare, especially handling poverty, is seen as quite significant in organizing social order, especially for the poor, where the distribution program carried out is divided into two categories, namely distribution. given to Muztahik, namely consumptive distribution and a productive distribution model. These two distribution models are equally given to those who fall into the Ashnaf category or those who fall into the poor category and are very deserving of receiving assistance, both consumptive and productive. Things like this are carried out by Baznas from the Regional or Regency level to the village level where there is a UPZ office or Zakat Collection Unit.